Left Atrial Myxoma with Mild Left Ventricular Dysfunction— A Case Report - Meher, T; Palash, SMAZN; Hasan, MK; Khan, TMNS; Zahangir, NM; Haider, MZ; Khan, SI; Devnath, CK; Ahmed, N; Ahmed, S (Pulse, 2018)
Atrial Myxoma is the most common primary cardiac tumors accounting for about 50% of benign primary cardiac tumors, with the majority located in the left atrium. This is a case of large left atrial (LA) myxoma presented with features of mitral stenosis associated with moderate left ventricular failure (LVF) and mild pulmonary artery hypertension (PAH) The patient improved markedly after tumor excision. Pulse Vol.10 January-December 2017 p.29-33